2010
DOI: 10.1186/bcr2496
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation therapy: targeting breast cancer stem cells to reduce resistance to radiotherapy and chemotherapy

Abstract: not available at time of publication. Abstract not available at time of publication. Retrospective studies on male breast cancer (MBC) have suff ered from small numbers of cases available from any one centre; thus a signifi cant problem in eff ectively studying this disease is accruing suffi ciently large numbers to allow comparative analysis of biomarkers associated with response. Using a coordinated multicentre approach, we present the fi rst large-scale study to address the relevance of the expression of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Similarly, Roy et al found that ATRA, trichostatin A and vorinostat caused dose-dependent decreases in the BCSC population, and showed that these differentiating agents reduced the number of BCSCs within the MCF7 cell line. Mammosphere formation in primary breast cancers (n = 3) was decreased by ≥ 25% by ATRA treatment combined with 6 Gy irradiation, compared with irradiation alone [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Roy et al found that ATRA, trichostatin A and vorinostat caused dose-dependent decreases in the BCSC population, and showed that these differentiating agents reduced the number of BCSCs within the MCF7 cell line. Mammosphere formation in primary breast cancers (n = 3) was decreased by ≥ 25% by ATRA treatment combined with 6 Gy irradiation, compared with irradiation alone [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to most other proapoptotic agents that preferentially target dividing cells, HDACis can induce apoptosis in nonproliferating cancer cell lines (52). Therefore, therapy through epigenetic drugs, such HDAC or DNA methyltransferase (DNMT) inhibitors, represents a particularly interesting and promising approach, as it is known that CSCs keep plasticity for differentiation (53). For instance, the demethylating agent 5‐aza‐2′‐deoxycytidine has been shown to inhibit self‐renewing population of CD34 + cells (54).…”
Section: Implications For Cancer Therapymentioning
confidence: 99%
“…Radiotherapy in breast cancer aims to decrease loco-regional spread of the disease [157,[223][224][225][226][227][228]. The therapy can be external beam radiation and internal beam radiation (also called brachytherapy) [229].…”
Section: Radiotherapymentioning
confidence: 99%